2016
DOI: 10.16965/ijims.2016.112
|View full text |Cite
|
Sign up to set email alerts
|

Birth Preparedness and Complication Readiness Plans among Antenatal Attendees at Primary Health Centre of District Jhansi, U.P, India

Abstract: BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
2
1
2
Order By: Relevance
“…In our study, 77.5% of the participants availed ANC service in the first trimester. Our findings are closely similar to the findings of Mukhopadhyay et al [ 15 ] and Gupta et al [ 2 ] However, in the study by Rajesh et al ,[ 13 ] 97% women had their ANC started in first trimester. Early registration of pregnancy results likely in a safer pregnancy and positive outcome.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, 77.5% of the participants availed ANC service in the first trimester. Our findings are closely similar to the findings of Mukhopadhyay et al [ 15 ] and Gupta et al [ 2 ] However, in the study by Rajesh et al ,[ 13 ] 97% women had their ANC started in first trimester. Early registration of pregnancy results likely in a safer pregnancy and positive outcome.…”
Section: Discussionsupporting
confidence: 92%
“…More than half (58.5%) women were found to be well prepared by fulfilling at least four indicators. BPACR index of our study was higher than that observed by Patil et al [ 7 ] (55.83%), Gupta et al [ 2 ] (46.2%), Acharya et al [ 10 ] (41%), Mazumdar et al [ 14 ] (49.4%), and Mukhopadhyay et al [ 15 ] (34.5%).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Most common reported danger sign was severe vaginal bleeding during pregnancy (51.3%), labour (43.4%), postpartum period (4.3%). A Similar response was obtained in the previous studies such as Agarwal S et al (7), Lliyasu Z et al(8), Gurung J et al (9), Acharya AS et al (10), Gupta S et al (11) and Smeele P et al (12) and Mandal T et al (13). In the present study, Difficult/ fast breathing was the most commonly answered danger signs in newborn given by 9.6%.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, BPACR index came out to be 62.3%. BPACR index of our study was lower than that observed by Sharma et al 13 (66.9%) on the contrary it was higher than that observed by Patil et al 14 Gupta et al 15 (46.2%), Acharya et al 12 (41%) and Mukhopadhyay et al 16 (34.5%). This study was conducted in a health care setup with antenatal women more than 20 weeks included in this study.…”
Section: Discussioncontrasting
confidence: 78%